Influences of TPB variable on SMEs intention to adopt online crowdfunding services in Nigeria - Kazaure, Mansur Ahmed; Abdullah, Abdul Rashid; Jantan, Amer Hamzah; Zawawi, Dahlia (Science and Engineering Research Support Society, 2020)
This study contributes to the existing literature on crowdfunding by examining the influences of TPB variable on SMEs intention to adopt crowdfunding service. SMEs in Nigeria faced with financial constraint, which affect their performance, growth and survival. Structural equation modeling (SEM) has been use to analysis a sample of 385 SMEs owners in three state of Kano, Kaduna and Katsina in Northwestern Nigeria. Four hypotheses found to be significant and one is not significant. The paper recommended that, actors in crowdfunding industry should use Social media channels to communicate the benefit of crowdfunding service in financing SMEs, because finding indicates that, used of social media and information are key variable in influencing SMEs intention to adopt crowdfunding services. The study has some limitation; cross-sectional approach was use in the current study, in which the data were collected at a single point of time. Consequently, it is recommended for the future research to employ longitudinal study.